Characterization of viral, bacterial, and parasitic causes of disease in small-scale chicken flocks in the Mekong Delta of Vietnam. - Van, NTB; Yen, NTP; Nhung, NT; Cuong, NV; Kiet, BT; Hoang, NV; Hien, VB; Chansiripornchai, N; Choisy, M; Ribas, A; Campbell, J; Thwaites, G; et al. (Elsevier, 2019)
In the Mekong Delta region of Vietnam, small-scale chicken farming is common. However, high levels of disease or mortality in such flocks impair economic development and challenge the livelihoods of many rural households. We investigated 61 diseased small-scale flocks (122 chickens) for evidence of infection with 5 bacteria, 4 viruses, and helminths. Serological profiles (ELISA) were also determined against 6 of these pathogens. The aims of this study were the following: (1) to investigate the prevalence of different pathogens and to compare the probability of detection of bacterial pathogens using PCR and culture; (2) to investigate the relationship between detection of organisms in birds' tissues and the observed morbidity and mortality, as well as their antibody profile; and (3) to characterize risk factors for infection with specific viral or bacterial pathogens. We used PCR to test for viral (viruses causing infectious bronchitis [IB], highly pathogenic avian influenza [HPAI], Newcastle disease, and infectious bursal disease [IBD]) and bacterial pathogens (Mycoplasma gallisepticum, Pasteurella multocida, Avibacterium paragallinarum, and Ornithobacterium rhinotracheale [ORT]). The latter two were also investigated in respiratory tissues by conventional culture. Colisepticemic Escherichia coli was investigated by liver or spleen culture. In 49 of 61 (80.3%) flocks, at least one bacterial or viral pathogen was detected, and in 29 (47.5%) flocks, more than one pathogen was detected. A. paragallinarum was detected in 62.3% flocks, followed by M. gallisepticum (26.2%), viruses causing IBD (24.6%) and IB (21.3%), septicemic E. coli (14.8%), ORT (13.1%), and HPAI viruses (4.9%). Of all flocks, 67.2% flocks were colonized by helminths. Mortality was highest among flocks infected with HPAI (100%, interquartile range [IQR]: 81.6-100%) and lowest with flocks infected with ORT (5.3%, IQR: 1.1-9.0%). The results indicated slight agreement (kappa ≤ 0.167) between detection by PCR and culture for both A. paragallinarum and ORT, as well as between the presence of cestodes and ORT infection (kappa = 0.317). Control of A. paragallinarum, viruses causing HPAI, IBD, and IB, M. gallisepticum, and gastrointestinal helminths should be a priority in small-scale flocks.